ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PEMBIAYAAN PADA BANK UMUM SYARIAH (STUDI PADA BANK UMUM SYARIAH TAHUN 2012-2015) - Nurrochman, Isnu; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2016)
Islamic Banking based on the Quran and al-Hadist in its operations by not using riba. Profit sharing financing in Islamic Banking product can reach the real sector to strengthen the Indonesian economy. But, Bai Finacing have a biggest financing by Islamic Banking. Therefore, this study aims to examines the factors that affect financing in Islamic Banking such Thrid Party Fund (DPK), Financing to Deposit Ratio (FDR), Return On Asset (ROA), Non Performing Financing (NPF), Inflation, and BI Rate. The sample used in this study consist of nine Islamic Banks in Indonesia 2012-2015 periods. The sampling technique used purposive sampling. The type of data using secondary data obtained from financial statement of Islamic Banks website, so it has 144 observational data. Data were analyzed with multiple regression analysis using SPSS version 21.The result from this study indicates factors that affect Financing in Islamic Banking such variables Thrid Party Fund (DPK), Financing to Deposit Ratio (FDR), Return On Asset (ROA), Non Performing Financing (NPF), and BI Rate significant positive effect on Financing. However, Inflation not significant impact on Financing. The amount of coefficient determination R2 (adjusted R2) is 0.812. That means the factors that affect financing such as DPK, FDR, ROA, NPF, Inflastion, and BI Rate have the impact on Financing of 81.2%. Meanwhile, the remaining 18.8% is explained by other variables outside the model of this study.